2006
DOI: 10.1007/s10763-006-9053-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective Professional Development in Science and Mathematics Education: Teachers' and Facilitators' Views

Abstract: This study compares the views of teachers and professional development facilitators about effective professional development (PD). We analyzed interviews with 72 teacher participants and 23 PD facilitators involved in nine science and mathematics PD projects. The teachers' themes for characterizing effective PD included classroom application, teacher as learner, and teacher networking. Similarly, the PD facilitators discussed effective PD as having classroom application and experiences for teachers as learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
25

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 16 publications
4
40
0
25
Order By: Relevance
“…For example, Park Rogers et al, (2007) found that both teachers and PD facilitators considered classroom application, teachers as learners, collegiality and collaboration as the important characteristics of PD. When Wilson and Berne (1999) observed PD and interviewed participants, teachers reported that they enjoyed PD that was relevant to their practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Park Rogers et al, (2007) found that both teachers and PD facilitators considered classroom application, teachers as learners, collegiality and collaboration as the important characteristics of PD. When Wilson and Berne (1999) observed PD and interviewed participants, teachers reported that they enjoyed PD that was relevant to their practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Los aprendizajes de las experiencias de formación continua de docentes más exitosas tienen que ver con el hecho de que en la mayoría de ellas se contó con espacios para el trabajo colaborativo que favorecían la reflexión y el cuestionamiento de las propias ideas y creencias (Park Rogers et al, 2007).…”
Section: Creencias Formación Docente Y Cambio Educativounclassified
“…Adult learning theory indicates that adults in their thirties and forties become more reflective and contextoriented (Sheehy, 1976), making it imperative that professional development programs engage participants in both metacognitive and concrete thought as they seek to improve both conceptions of teaching and learning and actual teaching practice. With this in mind, Rogers, Abell, and Lannin (2007) stress the importance of engaging teachers in complex thought instead of simply presenting them with information in order to challenge pedagogical knowledge and confront teachers with a transformative cognitive dissonance. An exemplary development program should engage its participants beyond the point of simply sitting and listening; discussion, reflection, and critical thinking are necessary if real learning is to take place.…”
Section: Standard B: Professional Development For Teachers Of Engineementioning
confidence: 99%